2015
DOI: 10.1080/18146627.2015.1110907
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ perceptions: The value of assessment rubrics for informing teaching practice and curriculum review and development

Abstract: The assessment rubric is increasingly gaining recognition as a valuable tool in teaching and learning in higher education. While many studies have examined the value of rubrics for students, research into the lecturers' usage of rubrics is limited. This article explores the lecturers' perceptions of rubrics, in particular, its use and design, the role it can play in informing one's teaching practice and in curriculum review and development. The data shows that many lecturers use the rubric in a very mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
(23 reference statements)
0
4
0
3
Order By: Relevance
“…Instead, it is necessary to consider several essential aspects when creating rubrics and using them in the classroom—e.g., involving students in their development, demonstrating their understanding and positive assessment as learning guides—[ 18 , 34 , 36 , 37 , 41 , 42 ]. Fewer studies analyze teachers’ perceptions and attitudes about rubrics, and they conclude that teachers mainly view them as more objective grading tools, but with limited formative value [ 18 , 20 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is necessary to consider several essential aspects when creating rubrics and using them in the classroom—e.g., involving students in their development, demonstrating their understanding and positive assessment as learning guides—[ 18 , 34 , 36 , 37 , 41 , 42 ]. Fewer studies analyze teachers’ perceptions and attitudes about rubrics, and they conclude that teachers mainly view them as more objective grading tools, but with limited formative value [ 18 , 20 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the point when utilized by a teacher as a piece of developmental evaluation, they can assist students with understanding both the all-encompassing nature and/or explicit examination of learning anticipated, level of learning expected, and afterward settle on a choice about the present degree of figuring out how to illuminate modification and improvement. Bhuruthram [11] showed with the experimental data that rubrics recognized as a important tool for the teacher's practice and in curriculum review and development. It is also showed that the rubrics helps the teacher to upgrade his teaching practice and course design.…”
Section: Review Of Literaturementioning
confidence: 91%
“…En este sentido, esta herramienta potencia mucho más la transparencia de la evaluación (Bearman y Ajjawi, 2021) al disponer el estudiante de criterios concretos y precisos (Jonsson, 2014). Wiggins (1998) sostiene que la autoevaluación es inseparable de cualquier evaluación que tenga como objetivo mejorar el aprendizaje, y hay que intentar que estas herramientas evaluativas de TFG sirvan para estos fines y no solamente con propósitos de clasificación o calificación (Bharuthram, 2015).…”
Section: Discusión Y Conclusionesunclassified